Celestial Shadows Eclipses, Transits, and Occultations - Westfall, John.; Sheehan, William; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
Much of what is known about the universe comes from the study of celestial shadows$1 (Beclipses, transits, and occultations. The most dramatic are total eclipses of the Sun, which constitute one of the most dramatic and awe-inspiring events of nature. Though once a source of consternation or dread, solar eclipses now lead thousands of amateur astronomers and eclipse-chasers to travel to remote points on the globe to savor their beauty and the adrenaline-rush of experiencing totality, and were long the only source of information about the hauntingly beautiful chromosphere and corona of the Sun. Long before Columbus, the curved shadow of the Earth on the Moon during a lunar eclipse revealed that we inhabit a round world. The rare and wonderful transits of Venus, which occur as it passes between the Earth and the Sun, inspired eighteenth century expeditions to measure the distance from the Earth to the Sun, while the recent transits of 2004 and 2012 were the most widely observed ever--and still produced results of great scientific value. Eclipses, transits and occultations involving the planets, their satellites, asteroids and stars have helped astronomers to work out the dimensions and shapes of celestial objects$1 (Beven, in some cases, hitherto unsuspected rings or atmospheres$1 (Band now transits have become leading tools for discovering and analyzing planets orbiting other stars. This book is a richly illustrated account of these dramatic and instructive astronomica l phenomena. Westfall and Sheehan have produced a comprehensive study that includes historical details about past observations of celestial shadows, what we have learned from them, and how present-day observers$1 (Bcasual or serious$1 (Bcan get the most out of their own observations. .s
Preface -- Part I. The Diversity of Eclipse Events -- Eclipse Phenomena -- The Waltz of the Planets -- The Performers -- Part II. A Transit Chronicle -- The Beginnings -- Scaling the Heavens -- A Century of Progress and Disappointment - and Completion -- Our Own Venus Transit - The June Flowers of 2004 -- Part III. 2012 - Our Last Chance for a Venus Transit -- The 2012 Event -- Observing the 2012 Transit -- Mercury also Transits the Sun -- Transits Galore -- The Splendor of a Solar Eclipse -- The Beauty of a Lunar Eclipse -- Planetary Satellites -- Occultations - When Blocking the View is Helpful -- Appendices -- References -- Index. .
Keywords: Physics; Planetology; Astronomy; Astrophysics; Cosmology; Physics; Astronomy, Astrophysics and Cosmology; Popular Science in Astronomy; Planetology; Electronic books